Profile of optical constants of SiO2 thin films containing Si nanocrystals - Dong, Gui (2010)
For optoelectronic and photonic applications of Si nanocrystals (nc-Si) embedded in a SiO2 matrix, the information of the depth profiles of the optical constants for the thin film system is necessary. In this work, an approach of the depth profiling for the thin film synthesized with ion implantation is developed. In this approach, the nc-Si depth distribution obtained from secondary ion mass spectroscopy measurement is modeled with the approximation of many sublayers, and for a given wavelength the optical constants of each sublayer are formulated with the nc-Si volume fraction in the sublayer and the nc-Si optical constants as variables based on the effective medium approximation. After the above procedures the nc-Si optical constants are obtained from the spectral ellipsometric fittings. Finally the optical constants of each sublayer are calculated, and thus the depth profiles of the optical constants for the SiO2 thin film containing the nc-Si are obtained.